1991
DOI: 10.1111/j.1471-4159.1991.tb08312.x
|View full text |Cite
|
Sign up to set email alerts
|

D1 Dopamine Receptors Can Interact with Both Stimulatory and Inhibitory Guanine Nucleotide Binding Proteins

Abstract: Pretreatment of striatal membranes with N-ethylmaleimide in the presence of a D1-specific agonist inactivated endogenous guanine nucleotide binding proteins (G proteins), but not D1 dopamine receptors, resulting in a loss of high-affinity agonist binding sites. Such D1 receptors were solubilized, mixed with exogenous G proteins from cells not containing D1 receptors, and reconstituted into phospholipid vesicles. These reconstituted receptors were able to couple to the exogenous G proteins, and the proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Mammalian DA receptors as well as other G-protein-coupled receptors (GPCRs) can couple different G proteins (Sidhu and Niznik, 2000). For example, D1 DA receptors are coupled to G s , G i , and G o (Sidhu et al, 1991), and D5 DA receptors are coupled to G s as well as G z , a pertussistoxin insensitive member of the G i/o family (Sidhu et al, 1998). Moreover, the cloned invertebrate Drosophila D1-like DA receptor, DopR99B, was found to be coupled to two different secondmessenger systems, cAMP and Ca 2þ (Reale et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian DA receptors as well as other G-protein-coupled receptors (GPCRs) can couple different G proteins (Sidhu and Niznik, 2000). For example, D1 DA receptors are coupled to G s , G i , and G o (Sidhu et al, 1991), and D5 DA receptors are coupled to G s as well as G z , a pertussistoxin insensitive member of the G i/o family (Sidhu et al, 1998). Moreover, the cloned invertebrate Drosophila D1-like DA receptor, DopR99B, was found to be coupled to two different secondmessenger systems, cAMP and Ca 2þ (Reale et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the change in G-protein usage between normal and transformed breast cells is not simply a matter of G-protein availability, because both G␣ i and G␣ s are expressed abundantly in both MMECs and Comma-D cells. It is well established that GPCRs often utilize different heterotrimeric G-proteins, but stable coupling of the same receptor to G␣ i and G␣ s is not a commonly reported pattern (55,56). Dynamic feedback switching from G␣ s to G␣ i usage has been documented to occur in response to ligand binding for several receptors, including the ␤1-and ␤2-adrenergic receptors, the prostacyclin receptor, and the vasoactive intestinal polypeptide receptor (45,(57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to address this issue, the molecular approach we and others have used has been to identify the nature of the G proteins that these receptors are coupled to. In 1991, when we ®rst suggested that D1like DA receptors couple to pertussis toxin-(PTX-)sensitive G proteins (such as G i a/G o a ) in addition to coupling to G s a, GPCRs were not thought to possess the intrinsic ability to couple to more than one G protein [67]. It is now, however, widely accepted that GPCRs can and do couple to several G proteins, enabling the simultaneous activation of multiple signaling pathways.…”
Section: Functional Properties Of Dopaminergic Receptorsmentioning
confidence: 99%
“…Through reconstitution studies, we initially demonstrated that soluble D1 receptors couple to both cholera toxin-(CTX-)sensitive, G s a, and PTX-sensitive, G i a/G o a, G proteins [67]. In rat pituitary GH 4 C 1 cells transfected with D1 cDNA, we found that even in the membrane-bound state, D-1 sites couple to CTX-and PTX-sensitive Ga [27,28].…”
Section: Coupling Of D1 Receptors To G Proteinsmentioning
confidence: 99%